Editorial: Peruvian and International Circumstances: Investment and Public Policies - El Director (2008)
We begin 2008 with the determination to continue encouraging research under the strictest parameters existing in the country. In this issue we publish an excerpt from the winning work in the 2007 research contest: “Education and labor income in Peru”, by Eduardo Quiróz and José Espinoza. The excerpt, which we have entitled Education and income: methodological aspects and studies in Peru, is devoted to mathematical formalizations and includes a review of the Peruvian bibliography on the impact of education on economic status; the analyses and conclusions of the study do not appear, as they will be the subject of a special publication. The respective contest for the present period has already been announced and we are receiving the projects.